2023
DOI: 10.1002/1873-3468.14573
|View full text |Cite
|
Sign up to set email alerts
|

The Chlamydia trachomatis p‐aminobenzoate synthase CADD is a manganese‐dependent oxygenase that uses its own amino acid residues as substrates

Abstract: Edited by Peter BrzezinskiCADD (chlamydia protein associating with death domains) is a paminobenzoate (pAB) synthase involved in a noncanonical route for tetrahydrofolate biosynthesis in Chlamydia trachomatis. Although previously implicated to employ a diiron cofactor, here, we show that pAB synthesis by CADD requires manganese and the physiological cofactor is most likely a heterodinuclear Mn/Fe cluster. Isotope-labeling experiments revealed that the two oxygen atoms in the carboxylic acid portion of pAB are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The cyclic nature of catalysis distinguishes FlcD from the characterized HDOs, all of which require auxiliary reductants for multiple turnovers. [11][12][13]15,16,[18][19][20]22,23 Overall, the spectroscopic findings suggest that the FlcD cofactor deviates from that of prototypical HDOs and more resembles that of mononuclear non-heme Fe-dependent oxidative enzymes.…”
Section: Crystal Structures Of Flcd Reveal the Presence Of A Mononucl...mentioning
confidence: 86%
See 1 more Smart Citation
“…The cyclic nature of catalysis distinguishes FlcD from the characterized HDOs, all of which require auxiliary reductants for multiple turnovers. [11][12][13]15,16,[18][19][20]22,23 Overall, the spectroscopic findings suggest that the FlcD cofactor deviates from that of prototypical HDOs and more resembles that of mononuclear non-heme Fe-dependent oxidative enzymes.…”
Section: Crystal Structures Of Flcd Reveal the Presence Of A Mononucl...mentioning
confidence: 86%
“… C hlamydia protein a ssociating with d eath d omains (CADD) catalyzes the cleavage between the α- and β-carbon of its active site tyrosine and an amination to generate para -aminobenzoic acid (Figure S1C). HDOs also introduce essential functionalities into the structures of therapeutically and ecologically important natural products. For example, SznF catalyzes consecutive N -hydroxylations of methylarginine in the biosynthesis of the anticancer agent streptozotocin (Figure S1B).…”
Section: Introductionmentioning
confidence: 99%
“…We next sought to further investigate the fate of Lys152 by using proteomics approaches. Another study reported the deamination and oxidation of this residue to aminoadipic acid, but results could not be specifically linked to catalysis due to the use of a low-activity preparation of the enzyme, sole-reconstitution with Mn, and additional modifications of Lys that can result from metal-catalyzed generation of reactive oxygen species. This region eluded detection in our previous proteomics study because complete trypsin digestion of CADD is expected to result in a dipeptide (EK 152 ) with an m / z value of 276, which is beyond the MS1 scan range ( m / z = 375–1600) of the liquid chromatography–mass spectrometry/MS (LC-MS/MS) method that was used.…”
mentioning
confidence: 99%
“…Unlike the HDOs that have been spectroscopically, ,, , or in the case of SznF and AetD, structurally verified to house a diiron cofactor, a recent reexamination of CADD metal-dependence has shown that the enzyme requires both Fe and Mn for efficient p ABA production . A later study by Wooldridge and colleagues confirmed the essential role played by Mn for CADD activity . However, the most surprising facet of the p ABA assembly is that an exogenous substrate is not required.…”
mentioning
confidence: 99%
See 1 more Smart Citation